Get out of my bath! - Teckentrup, Britta (Nosy Crow, an imprint of Candlewick Press, 2015)
Ellie the elephant's relaxing bath is disrupted by splashing friends, prompting her to suck up all of the water into her trunk until everyone else leaves.